An Assessment of Knowledge and Attitude Regarding Animal Suffering and Rights among University Students in Punjab, Pakistan - Sungat Balouch; Eram Jamil; Muhammad Mohsin Khan (Journal of Management Practices, Humanities and Social Sciences, 2022)
In the social sciences, assessment of societal attitudes toward animals’ rights is very important to understand the relationship between science and the normative pattern of society. In the present study, a survey was carried out to determine the knowledge and attitude of Pakistani university students toward animal suffering and rights. By reviewing existing literature, limited studies were carried out in Pakistan. A random sampling technique was used in which an online cross-sectional study was conducted, and 200 respondent students participated in the survey from different public-sector universities in the province of Punjab, Pakistan. The data was collected through a web-based questionnaire. The questions were designed to explain the respondents' views toward animals' suffering and rights while keeping in view the cultural and religious perspectives. Study results demonstrated that a surprising majority of students, including ladies and men (55% p 0.05), were not well aware of animal rights. About 49.4% of respondents did not consider it an injustice, while 51.8% considered it right to kill the animals to achieve trophies. Furthermore, it has been observed that about 84% (p 0.05) were in favor of the adoption of pets. The level of attitudes toward animal care varies concerning age, education, and residency in rural or urban areas; however, the trend remains equal in each gender. In short, students do not know about animal rights. Considering how important animal rights are, this study showed that the Higher Education Commission of Pakistan needs to hold workshops and awareness campaigns in universities to teach students about animal rights and how to protect them.